The Use of Hemodialysis in Refractory Hypercalcemia Secondary to Parathyroid Carcinoma - Huai Heng Loh; Nurain Mohd Noor (Case Reports in Critical Care)
Parathyroid carcinoma is a rare cause of hypercalcemia. Hypercalcemic crisis is a medical emergency. Hemodialysis is rarely needed to treat hypercalcaemia. We report a case of refractory hypercalcaemia secondary to parathyroid carcinoma requiring haemodialysis.